Evaluating the effects of low-dose simulated galactic cosmic rays on murine hippocampal-dependent cognitive performance - Simmons, Pilar; Trujillo, Madison; McElroy, Taylor; Binz, Regina; Pathak, Rupak; Allen, Antiño R. (Frontiers in Neuroscience, 2022)
Space exploration has advanced substantially over recent decades and plans to increase the duration of deep space missions are in preparation. One of the primary health concerns is potential damage to the central nervous system (CNS), resulting in loss of cognitive abilities and function. The majority of ground-based research on space radiation-induced health risks has been conducted using single particle simulations, which do not effectively model real-world scenarios. Thus, to improve the safety of space missions, we must expand our understanding of the effects of simulated galactic cosmic rays (GCRs) on the CNS. To assess the effects of low-dose GCR, we subjected 6-month-old male BALB/c mice to 50 cGy GCR (1H, 28Si, 4He, 16O, and 56Fe) whole-body irradiation at the NASA Space Radiation Laboratory. Animals were tested for cognitive performance with Y-maze and Morris water maze tests 3 months after irradiation. Irradiated animals had impaired short-term memory and lacked spatial memory retention on day 5 of the probe trial. Glial cell analysis by flow cytometry showed no significant increase in oligodendrocytes, astrocytes, microglia or neural precursor cells (NPC’s) between the sham group and GCR group. Cytogenetic data showed a significant increase in the frequency of chromosomal aberrations after GCR exposure. Finally, tandem mass tag proteomics identified 3,639 proteins, 113 of which were differentially expressed when comparing sham versus GCR exposure (fold change >1.5; p <0.05). Our data suggest exposure to low-dose GCR induces cognitive deficits by impairing short-term memory and spatial memory retention.